BIOBRIQUETTE PRODUCTION FROM PALM FRONDS AND SHELLS: EFFECT OF MATERIAL COMPOSITION AND PARTICLE SIZE - Okta Bani; Iriany; Taslim; Cici Novita Sari; Cindy Carnella (Talenta Publisher (Universitas Sumatera Utara), 2018)
Briquettes are solid fuels from organic materials with high calorific values ​​and burn duration. The composition and particle size of the raw material may affect briquette quality. This study aimed to evaluate the effect of composition and particle size on calorific value and characteristics of the resulting briquettes. In this study, briquettes were made using palm oil fronds and shells at mass ratio of 1:2, 1:4, 1:6, 1:8 and particle size of not-dertemined, 50, 70, and 100 mesh. First, raw material was carbonized at 450°C for 30 minutes then added to 20%wt. starch glue and waste oil (1:1 ratio). Resulting briquettes were analyzed for its water content, ash content, density, volatile matter content, fixed carbon content, combustion rate, calorific value, and compressive strength. Satisfying results were obtained for briquettes with a front to shell ratio of 1:8, and a particle size of 100 mesh. At this condition, the resulting briquettes have water content of 5.5%; ash content of 2.54%; density of 0.51 g/cm3; 19.58% vapor content; fixed carbon content of 72.38%; combustion rate of 0.2 g/min (3.4×10-3 g/sec); calorific value of 15.3 kcal/g; and compressive strength of 0.06 N/mm2. These results have complied with the Indonesian National Standard (SNI), Japanese, American, and English standards, except for briquette compressive strength, which have not met the industrial standard.